2008
DOI: 10.1016/j.jvs.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Infrapopliteal arterial revascularization for critical limb ischemia: Is the peroneal artery at the distal third a suitable outflow vessel?

Abstract: Revascularization to the distal third of the PA can achieve much the same outcome in terms of patency and limb salvage rates, wound healing rate and timing, as when other inframalleolar or pedal branches are used. The skepticism surrounding use of the terminal PA as an outflow vessel appears to be unwarranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…In a retrospective series of 420 consecutive diabetic patients, Faglia et al observed that the reperfusion through the peroneal artery alone is not sufficient to avoid major amputation in some patients, but author did not analyze the peroneal distal branches patency [6]. However, other authors have found similar clinical results between peroneal artery and other tibial arteries after endovascular [25] or surgical bypass procedures [26]. In this sense, we argue that the disparity of the results between publications that have focused on foot outflow vessels could be explained in part by the lack of a foot anatomical ulcer classification and the absence of data about foot and ankle collateral patency in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective series of 420 consecutive diabetic patients, Faglia et al observed that the reperfusion through the peroneal artery alone is not sufficient to avoid major amputation in some patients, but author did not analyze the peroneal distal branches patency [6]. However, other authors have found similar clinical results between peroneal artery and other tibial arteries after endovascular [25] or surgical bypass procedures [26]. In this sense, we argue that the disparity of the results between publications that have focused on foot outflow vessels could be explained in part by the lack of a foot anatomical ulcer classification and the absence of data about foot and ankle collateral patency in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…7,[13][14][15][16] Unlike an earlier analysis that identified different patency rates at tibial level, 14 but consistently with other authors, 8 we found that performing IARs with tibial arteries as target outflow vessels did not significantly affect the long-term patency and limb salvage rates in our two groups and subgroups, confirming previous findings of ours reported elsewhere. 17,19,20 Adopting an intensive postoperative protocol of graft surveillance led to many prophylactic lesion revisions being performed successfully in both sexes, explaining the marked improvement in the patency rates for failing (assisted primary patency) and failed revascularizations (secondary patency) at all intervals in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…18 The peroneal artery was always exposed using a lateral approach requiring segmental fibulectomy. 19 The dorsalis pedis artery was often chosen as the outflow target artery as an alternative to a patent peroneal artery and when no tibial vessels were in direct continuity with the foot. Revascularization to the dorsalis pedis artery was avoided in cases of severe dorsal foot infection.…”
Section: Methodsmentioning
confidence: 99%
“…The number of patients suffering from chronic hind limb ischemia is increasing, and these patients urgently need revascularization treatment 1, 2. Angiogenesis originates from the proliferation and migration of endothelial cells and contributes to the formation of collateral circulation 3.…”
Section: Introductionmentioning
confidence: 99%